The Philosophical Relevance and Constitutional Limits of Islamic Constitutionalism in Indonesia - Madhur M; Bulkini Sasu (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
he Indonesian Constitution is founded upon Pancasila and the 1945 Constitution as the philosophical and constitutional basis of the state. As the world’s largest Muslim-majority nation, Indonesia also reflects Islamic constitutional values in the development of its legal system, creating an ongoing debate regarding their relevance and constitutional limits within a pluralistic democratic state. This study aims to examine the relevance of Islamic constitutional principles as a philosophical foundation of the Indonesian Constitution while identifying the constitutional boundaries governing their application. The research employs a normative legal method using statutory, conceptual, historical, and comparative approaches to analyze constitutional doctrines, legal principles, and scholarly perspectives. The findings demonstrate that universal Islamic constitutional values—including justice, deliberation (shura), equality before the law, human rights protection, public welfare (maslahah), and the rule of law—are substantially compatible with the constitutional values embodied in Pancasila and the 1945 Constitution. Nevertheless, these principles function as ethical and philosophical references rather than formal constitutional sources. Their implementation must remain consistent with constitutional supremacy, democratic governance, legal certainty, and the protection of the rights of all citizens regardless of religious affiliation. This study contributes to constitutional scholarship by proposing an integrative conceptual framework that reconciles Islamic constitutional values with Indonesia’s constitutional order, strengthening constitutional theory grounded in religious ethics while preserving democracy, pluralism, and the rule of law.